공항 수용량 산정 동향 - 이승준; 이주환; 백호종; Seungjun Lee; Juhwan Lee; Hojong Baik (한국항공운항학회지, 2024)
The continuous increase in air traffic causes airport congestion and inconvenience to passengers using the airport. Saturation of capacity is one of the factors that lowers the level of service of the airport, and it affects not only inconvenience caused by flight delays but also economic losses such as increased fuel consumption due to waiting. Therefore, it cannot be overlooked to frequently estimate and evaluate the capacity of existing airport facilities in accordance with increasing demand. In this study, the overall trend of airport capacity estimation in the past was analyzed and how it was applied was studied. Prior to analyzing the trend of capacity estimation, it was possible to define it as aircraft throughput per unit time through a literature study on the definition of airport capacity. Airport capacity estimation methods can be divided into macroscopic and microscopic methods. Absolute capacity can be calculated in a macroscopic analysis, and practical capacity can be calculated in a microscopic analysis. The biggest factor that differentiates absolute capacity from practical capacity is whether or not delay is reflected. In the case of absolute capacity, the delay is not reflected, but in the case of practical capacity, the capacity is calculated considering the delay. In addition, the absolute capacity uses a calculation formula to calculate the capacity relatively intuitively and simply, that is, macroscopically, and the practical capacity can calculate the capacity microscopically as the model is relatively specific using a simulation model.